Immunization of cattle with a Rhipicephalus microplus chitinase peptide containing predicted B-cell epitopes reduces tick biological fitness - María Martina Esperanza Perez-Soria; Daniel Gustavo López-Díaz; Rafael Jiménez-Ocampo; Gabriela Aguilar-Tipacamú; Massaro W. Ueti; Juan Mosqueda; Ala Tabor (Parasitology)
Rhipicephalus microplus, the cattle fever tick, is the most important ectoparasite impacting the livestock industry worldwide. Overreliance on chemical treatments for tick control has led to the emergence of acaricide-resistant ticks and environmental contamination. An immunological strategy based on vaccines offers an alternative approach to tick control. To develop novel tick vaccines, it is crucial to identify and evaluate antigens capable of generating protection in cattle. Chitinases are enzymes that degrade older chitin at the time of moulting, therefore allowing interstadial metamorphosis. In this study, 1 R. microplus chitinase was identified and its capacity to reduce fitness in ticks fed on immunized cattle was evaluated. First, the predicted amino acid sequence was determined in 4 isolates and their similarity was analysed by bioinformatics. Four peptides containing predicted B-cell epitopes were designed. The immunogenicity of each peptide was assessed by inoculating 2 cattle, 4 times at 21 days intervals, and the antibody response was verified by indirect ELISA. A challenge experiment was conducted with those peptides that were immunogenic. The chitinase gene was successfully amplified and sequenced, enabling comparison with reference strains. Notably, a 99.32% identity and 99.84% similarity were ascertained among the sequences. Furthermore, native protein recognition was demonstrated through western blot assays. Chitinase peptide 3 reduced the weight and oviposition of engorged ticks, as well as larvae viability, exhibiting a 71% efficacy. Therefore, chitinase 3 emerges as a viable vaccine candidate, holding promise for its integration into a multiantigenic vaccine against R. microplus.